Sensor eletroquímico baseado em óxido de grafeno reduzido e estanato de zinco para determinação de prometazina - Moreira, Andreza Lopes (2024)
A sensor based on a glassy carbon electrode modified with a composite of reduced graphene oxide and zinc stannate (Zn2SnO4-rGO/GCE) was developed for the detection and quantification of promethazine hydrochloride (PMZ) in pharmaceutical formulations, by means of square wave voltammetry (SWV). The obtained scanning electron microscopy (SEM) images indicated the aggregation between the rGO and Zn2SnO4 species. The chemical synergism between these components was observed by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV), by the lower resistance to charge transfer and the higher analytical signal in the oxidation process, when compared to the species separately. The characterization of the electrochemical behavior of PMZ on Zn2SnO4-rGO/GCE suggested an almost-reversible oxidation process controlled by diffusion-adsorption with the involvement of two electrons. The optimized SWV experimental conditions were Mcllvaine buffer pH 5.0, frequency of potential pulse application of 80 s−1, amplitude of potential pulses of 25 mV and potential pulse increment of 2 mV. The analytical curve obtained showed a linearity range of 1.48×10−7to 6.48×10−6 mol L−1 with R2 = 0.998 and limit of detection (LOD) and quantification (LOQ) values equal to 1.24×10−8 and 3.76×10−8 mol L−1, respectively. These values were compared to those obtained by molecular absorption spectroscopy in the ultraviolet and visible region (UV-Vis). In addition to presenting excellent repeatability (%RSD = 1.54; n = 12) and reproducibility (%RSD = 1.89; n = 7) values, the developed sensor was successfully applied in the determination of PMZ in commercial pharmaceutical tablet samples, presenting an average recovery rate of 96.62% (%RSD = 1.2).